SOSIALISASI DAN PENDAMPINGAN SISTEM PENCATATAN AKUNTANSI DASAR PADA UMKM DI DESA MANGKUNG - Solatiyah, Baiq; Muttalib, Abdul (Lembaga Dongan Dosen, 2023)
This community service activity aims to provide education and assistance to MSMEs in Mangkung Village by providing an understanding of the basics of accounting. The benefits that can be taken by training participants are: 1) MSME players can understand the basics of bookkeeping in their business transactions, 2) MSME players can make simple bookkeeping, 3) MSME players can know production costs so they know the profit from the business so that it is easier to manage strategy in business development, 4) MSME players can separate living costs from business costs. The method of implementing community service activities is carried out in several stages, namely the planning stage, preparation stage, implementation stage and evaluation stage.